EGGS AND EARLY LARVAE OF THE SAND WHITING, SILLAGO SIHAMA (FORSSKAL) - Bensam, P (Indian Journal of Fisheries, 2011)
Planktonic eggs of S. sihama have been identified from Mandapam in the south-east coast, based on similarities in the ripe ovarian eggs as well as other characters. The ripe ova range in diameter from 0.53 to 0.78 mm, have a single oilglobule in the diameter range of 0.150 to 0.167 mm and show faint vacuolation of yolk. The planktonic eggs have diameter range of 0.55 to 0.89 mm, in various stages of development, the size gradually increasing with progressive development. The oil globules show the same diameter range as that of the ripe ova and the yolk has faint vacuolation. In early embryos melanophores appear on the oilglobule and dorsal side of the head. With more development, the above pigmentation increases on the body also, accompanied by the appearance of diffused xanthophores. Hatching takes place in the afternoon of the day of collection, the newly hatched larva measuring 1.54 mm and its pigmentation is in the form of melanophores and diffused xanthophores. The 24-hours old larva measures 2.42 mm, with melanophores mostly along the dorsal and ventral margins of the body and xanthophores in the form of five vertical bands. By 48-hours (measuring 2.56 mm), the post larval phase has set in, with pigmentation of the eyes, formation of the mouth, etc. The similarities of the present material with those of the eggs and early larvae of S.japonica as well as the difference from it, are discussed